Effects of all-trans retinoic acid and oxygen concentration on the proliferation and differentiation of subcutaneous adipocytes in yak - Yasenjian, Sibinuer; Shan, Su; Zhe, Yuqi; Zhang, Yuqing; Chai, Zhixin (Frontiers in Veterinary Science, 2025)
In this study, we investigated the mechanism by which all-trans retinoic acid (ATRA) regulates the hypoxic adaptation of yak subcutaneous adipocytes through a dose-dependent regulation. The effects of different concentrations of ATRA (10 nM−10 μM) on cell proliferation and differentiation, lipid metabolism and key gene expression were analyzed by simulating a hypoxic environment (1% O2) in vitro. In the hypoxia model, ATRA showed biphasic regulation: the hypoxic environment inhibited cell survival, while low concentrations of ATRA (10–100 nM) significantly enhanced hypoxic cell survival and repaired lipid droplet accumulation by activating the PCNA/PPAR-γ signaling axis; while high concentrations of ATRA (1–10 μM) induced apoptosis and inhibited differentiation by upregulating BAX and inhibited differentiation, and its toxic effects were exacerbated by the hypoxic environment. In addition, a certain concentration (10–100 nM) of ATRA antagonized the hypoxia-induced HIF-1α pathway and regulated hypoxia-induced metabolic reprogramming via PCNA/PPAR-γ. The study revealed a dose-dependent bidirectional regulatory mechanism of ATRA in the hypoxic adaptation of yak adipocytes, which provides a new perspective for analyzing the energy metabolism strategy of plateau species.